2021
DOI: 10.3390/ph14030282
|View full text |Cite
|
Sign up to set email alerts
|

Marine-Derived Natural Products as ATP-Competitive mTOR Kinase Inhibitors for Cancer Therapeutics

Abstract: The mammalian target of rapamycin (mTOR) is a serine/threonine kinase portraying a quintessential role in cellular proliferation and survival. Aberrations in the mTOR signaling pathway have been reported in numerous cancers including thyroid, lung, gastric and ovarian cancer, thus making it a therapeutic target. To attain this objective, an in silico investigation was designed, employing a pharmacophore modeling approach. A structure-based pharmacophore (SBP) model exploiting the key features of a selective mT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 78 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…A high percentage of all the available therapeutic drugs are derived from natural plants, microbes or animal compounds [ 7 ]. Terrestrial and aquatic species of plants and microorganisms produce unique bioactive substances that can help in the development of standardized phytomedicines with proof of quality, safety and efficacy [ 4 , 5 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high percentage of all the available therapeutic drugs are derived from natural plants, microbes or animal compounds [ 7 ]. Terrestrial and aquatic species of plants and microorganisms produce unique bioactive substances that can help in the development of standardized phytomedicines with proof of quality, safety and efficacy [ 4 , 5 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This decoy set validation was initiated by the DS Ligand Pharmacophore Mapping module, which retrieved the four inhibitors used in pharmacophore generation from a given external database of 100 compounds (4 active + 96 decoys). Accordingly, the goodness of fit (GF) score was calculated as 0.72, which was found near the ideal model range value of 1 ( Table 2 ) [ 44 , 45 ]. The value of the GF score confirmed that our model is robust for further predicting active and potent Hpse compounds from an external database reasonably well.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of a receptor–ligand (structure-based) pharmacophore model relies on the catalytically active site of a protein and its interaction with the bound co-crystallized ligand. 28 The knowledge acquired from the model aids in identification of essential pharmacophoric features required for a protein's inhibition. 29 The crystal structure of RET tyrosine kinase complexed with a pyrazolopyrimidine inhibitor, PP1 (1- tert -butyl-3- p -tolyl-1 H -pyrazolo[3,4- d ]pyrimidin-4-ylamine) (PDB ID: 2IVV) was downloaded from Protein Data Bank (PDB) repository for pharmacophore generation.…”
Section: Methodsmentioning
confidence: 99%
“…The GH approach thereby generates a goodness of t (GF) score which ranges between 0 (null model) and 1 (ideal model). 28,33,34 The GF score is calculated on the basis of below equation, where D stands for the dataset encompassing active as well as inactive compounds, A represents the active compounds within D, Ht denotes the hit molecules which are retrieved by the generated pharmacophore model and Ha represents the total number of active hit compounds acquired by the model. The validation of the model was also checked via the Receiver Operating Characteristic (ROC) curve and the results were assessed on the basis of the area under the curve (AUC).…”
Section: Decoy Set Validation Of Generated Modelmentioning
confidence: 99%